Pemanfaatan Media Sosial oleh Mahasiswa di Lingkungan Kampus Kota Pematangsiantar dalam Memperkuat Identitas Nasional - Vincentius Danu Bona Arta Nadeak; Rosvita G.E Manurung; Kerin Junita Aristia Siringoringo; Afriyani Damanik; Adelisa Oktavia Manalu; Daulat Nathanael Banjarnahor (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to explore in depth the role of social media in strengthening the national identity of students in the Pematangsiantar City campus environment. National identity is seen as an important aspect in shaping the national consciousness of the younger generation, especially students who are in a critical phase of intellectual and social development. The research method used is a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation of students from various universities in Pematangsiantar City. The results show that students actively use social media to access, produce, and share content related to local culture, national history, national figures, and national issues relevant to their daily lives. Social media functions not only as a means of communication, but also as a space for expression and creativity that allows students to build national narratives independently, critically, and innovatively. The discussion emphasizes that amidst the rapid flow of globalization and the penetration of foreign cultures, social media plays a strategic role in maintaining national values, provided its use is directed in a reflective, educational, and responsible manner. In addition, social media has the potential to expand the reach of the dissemination of nationalist values in a more engaging way and in accordance with the communication style of the younger generation. The conclusion of this study emphasizes that social media can be an effective tool in shaping and strengthening national consciousness among students. This impact is long-term, contributing to character formation, national loyalty, and strengthening students' role as agents of change in maintaining national unity and integrity.